MEGAFAST MONSTER TRUCKS - Farndon, John; Edwards, Mat; Pyke, Jeremy (Edinbridge Kent, Great Britain : Hungry Tomato Ltd, 2015)
Megafast planes discovers the meaning of supersonic aircraft with the NASA Hyper X-43 scramjet, the NAA X-15 rocket plane, the Lockheed SR-71 and more. Learn what it means to break the sound barrier.
"SCORCH THE EARTH ON GIANT MACHINES" - coverpage
Includes index.
Keywords: Monster trucks -- Juvenile literature; Monster trucks -- Juvenile literature -- Speed